К вопросу о значении предлога - Карпов, Л. (Kalbotyra, 1974)
In this paper paradigmatic and syntagmatic relations of prepositions are discussed. A preposition enters into syntagmatic relations with the other units of the same level with which it occur and which constitute its context. But when some prepositions are in the complementary distribution we say that they represent one abstract preposition and constitute a syntagmatic set of prepositions. Therefore, paradigmatic relations are oppositions between syntagmatic sets of prepositions. The notion of diagnostic environments reflects relational hierarchy of prepositions. Speech-meaning a prepositions is determined by the following factors: 1) lexical meaning of the context components 2) grammatical properties of these components, 3) grammatical structure of the sentence, 4) conceptual structure of the sentence, 5) interrelations between manifestations of the same abstract prepositions in different environments, 6) central syntagmatic oppositions of prepositions, 7) peripheral syntagmatic oppositions of prepositions. Language-meaning of prepositions is determined by the paradigmatic relations, i. e. by the oppositions of syntagmatic sets of prepositions. The notion of non-full syntagmatic set reflects the connexion between speech-level and language-level prepositions.